THE EFFECT OF SCIENTIFIC APPROACH ON ELEMENTARY SCHOOL STUDENTS' LEARNING OUTCOMES IN SCIENCE LEARNING - Yanti Fitria; Ary Kiswanto Kenedi; Suang Kupon Syukur (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2021)
AbstractThis research motivated was the low science learning results of elementary school students as a need for a learning approach that can improve the learning outcomes of elementary school students. The purpose of this research was to determine the influence of scientific approaches on students' learning outcomes of science learning in elementary schools. This research is an experimental study. The research instruments used was study test results. The results of the research with the calculation of t-test obtained the value t-count = 2,179 while t-table = 1,680 where t-count > t-table then H0 is rejected and H1 is accepted. These results confirm that there is an influence of scientific approaches on students' learning outcomes in science learning. The implication of this research can be used as a reference for teachers in improving the science learning outcomes of elementary school.Keywords: scientific approach, learning outcomes, elementary school